The Role of Teachers in Creating an Effective Arabic Language Learning Environment at MTs NW Karang Baru - Eti Ulpiani; Hafizatun Nafis; Fadilah Amir; Aulia putri Anjani Dewi; Ahamd Rifa'i; Afyati; Adinda Rizki Hidayanti; Edi Hendriawan (Formad English Foundation NTB Jakarta, 2026)
Arabic language learning in Islamic schools requires not only appropriate instructional strategies but also a supportive learning environment shaped largely by the teacher. This study aimed to describe the role of teachers in creating an effective Arabic language learning environment at MTs NW Karang Baru, focusing on teachers’ efforts to establish a conducive atmosphere, the challenges they encountered, and the impact of these efforts on learning effectiveness. The research employed a qualitative approach with a descriptive design. Data were collected through classroom observations, interviews with Arabic teachers and students, and documentation of instructional materials, and were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that teachers contributed to an effective Arabic learning environment through structured lesson planning, the use of varied instructional methods, the consistent habituation of Arabic use in classroom interactions, and the utilization of learning media. However, teachers faced several constraints, including students’ low learning motivation, differences in learner abilities, limited facilities and instructional media, and substantial administrative workloads. Despite these challenges, teachers’ efforts positively influenced the learning process and outcomes, as reflected in increased student participation, improved comprehension and Arabic language skills, and the development of more positive attitudes toward Arabic learning. These findings highlight the teacher’s central role as a key factor in enhancing the quality of Arabic language learning environments in madrasah contexts.